Some innovative methods of the civil service personnel management in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
Personnel management is the main factor of modern society economic success. This significantlychanges the very concept of “human resources management” - it goes from a simple prompt solution tothe determination of problems arising the definition of people future needs, as well as the developmentof both their labor and creative potential. In this regard, it should be emphasized that in business, especiallyin large-scale one Personnel management is focused on solving strategic tasks of the organizationinnovative development, in other words, its goals and principles must comply with the organizationbasic strategic concept, and the function of personnel management must be taken into account whendeveloping the organization strategy. The aim of the study is to determine the new technologies effectivenessin public administration. This is called service-oriented thinking. In short, service systems arethe location of systems that create value and include people sharing information, technology and organizations,as well as language, measures, models, laws, etc. The main carrier of new competitive ideas,solutions, non-standard tasks or new ways of solving standard problems is the personnel. Creation of anefficient and effective system of public administration is a necessary condition for ensuring the dynamicsocial and economic development of our country. Therefore, the number one task remains to improvethe effectiveness of public administration, strict observance of the rule of law by state officials, and theprovision of high-quality public services to the public. Thus, the urgency of researching innovative methodsof the personnel management system in a state institution is due to the need for timely formationand development of innovative mechanisms for making managerial decisions that are adequate to therequirements of the modern economy, scientific and technical and information progress. Analyzing theforeign experience of the above countries, it should be noted a number of features that are of practical interestand can be taken into account in the process of improving the public service system of Kazakhstan:- in the countries examined, the professionalization of the state apparatus is carried out on an ongoingbasis;- flexible methods of human resources management (personnel management);- there are mechanisms for transferring the best employees with experience between the public andprivate sectors.Analyzing the experience of foreign countries, it is necessary to determine the level of public confidencein the system of competitive selection and the level of confidence of civil servants and citizens inthe mechanism for implementing the principles of meritocracy, that is, raising the career ladder with merit.During the development of innovative methods, knowledge of the program being implemented in thepublic service is acquired; knowledge of the best personnel technologies used in the modern public serviceof foreign countries; knowledge of the possibilities and limitations of the use of traditional and innovativehuman resources management tools in the civil service management practice; the ability to make a reasonablechoice of a specific staff tool, taking into account the purposes of its application, as well as the specificsof the given situation; skills of developing procedures and documents by the personnel department.This is called service-oriented thinking. In short, service systems are the location of systems that createvalue and include people, share information, technologies and organizations, as well as language,measures, models, laws, and so on.